Heusler 4.0: Tunable Materials - Wollmann, Lukas; Nayak, Ajaya K.; Parkin, Stuart S. P.; Felser, Claudia (Annual Reviews Inc., 2017)
Heusler compounds are a large family of binary, ternary, and quaternary compounds that exhibit a wide range of properties of both fundamental and potential technological interest. The extensive tunability of the Heusler compounds through chemical substitutions and structural motifs makes the family especially interesting. In this article we highlight recent major developments in the field of Heusler compounds and put these in the historical context. The evolution of the Heusler compounds can be described by four major periods of research. In the latest period, Heusler 4.0 has led to the observation of a variety of properties derived from topology that includes topological metals with Weyl and Dirac points; a variety of noncollinear spin textures, including the very recent observation of skyrmions at room temperature; and giant anomalous Hall effects in antiferromagnetic Heuslers with triangular magnetic structures. Here we give a comprehensive overview of these major achievements and set research into Heusler materials within the context of recent emerging trends in condensed matter physics.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Half-Heusler compounds; Half-metallic ferromagnetism; Noncollinear magnetic order; Tetragonal Heusler compounds; Topological materials; Weyl semimetals